Lithium slag morphology regulation and control method and application

Through hydrothermal reaction, the morphology of lithium slag is regulated, and the problems of insufficient utilization of lithium slag and environmental pollution are solved, and the performance improvement of lithium slag/PVC composite materials and the simplification of industrial production are achieved.

CN119823598AActive Publication Date: 2025-04-15FUZHOU UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510097689.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-15
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize lithium slag, resulting in large amounts of storage and environmental pollution, and the application of lithium slag in thermoplastic composite materials is limited.

Method used

By mixing lithium slag with caustic solution and morphological regulator, hydrothermal reaction is carried out to regulate the morphology of lithium slag, and forming lithium slag with long columnar morphology, thereby improving its application performance in PVC composite materials.

Benefits of technology

The morphological regulation of lithium slag has been achieved, the applicable environment has been broadened, environmental pollution has been reduced, the mechanical properties of lithium slag/PVC composite materials have been improved, and the production cost has been reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823598A_ABST
    Figure CN119823598A_ABST
Patent Text Reader

Abstract

The invention provides a lithium slag morphology regulation and control method and application, and the method comprises the following steps: preparing caustic alkali solutions with different concentrations, adding a certain mass of lithium slag and a morphology regulation and control agent into a reaction kettle, and carrying out a reaction to obtain long-column-shaped lithium slag. On the basis of resource utilization of the lithium slag, the lithium slag with different morphologies is added into the PVC material, the influence of the lithium slag with different morphologies on the performance of the PVC composite material is compared, and the lithium slag morphology which has more advantages on improvement of the performance of the PVC material is screened out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary utilization of waste resources, and specifically relates to a lithium slag morphology control method and application. Background Art

[0002] With the global green and low-carbon transformation and the rapid development of new energy vehicles, the strategic position of lithium resources has become increasingly prominent. At present, the main way to obtain lithium resources is to extract lithium from ores. Spodumene, lithium mica, iron lithium mica, and lithium feldspar are the main raw materials for lithium extraction from ores. A large amount of lithium extraction slag will be produced during the lithium extraction process, and a large amount of tailings will be produced during the mineral processing process. At present, the utilization of ore extraction slag is far less than the production of lithium extraction slag. Most of the lithium extraction slag is still treated by open-air stacking and landfill, which will pollute the soil environment and water resources. Exploring the application of lithium slag can further reduce pollution and reduce industrial production costs, which is of great significance to environmental protection and the economy.

[0003] Thermoplastic polymer materials (PVC, PP, HDPE, etc.) have a wide range of applications and are in demand in many industries, including the construction industry (doors and windows, pipes, cables), electronics, and automobiles. Its material performance advantages include weather resistance, acid and alkali resistance, and flame retardancy. The performance of thermoplastic materials can be optimized according to actual needs. At present, the modification of thermoplastic materials is mostly done by adding various functional additives or by adding inorganic fillers (titanium dioxide, talc or calcium silicate) with high costs to improve the performance of thermoplastic composite materials. The research on lithium slag as a filler to modify thermoplastic materials is mostly focused on the amount of additives and modification methods.

[0004] Patent CN101987897A discloses that a thermoplastic composite material prepared by mixing thermoplastic resin (HDPE), lithium mica and processing aid has good antistatic effect, but poor tensile strength (17~28Ma).

[0005] Patent CN117384453A discloses a high-strength and weather-resistant composite material and its preparation process. Tailings slag, steel sand, etc. are used as fillers and mixed with PVC, silane coupling agent, and processing aid to prepare a composite PVC composite material with high strength and weather resistance. However, the amount of processing aid used is large, which is 4.25~13.25% of the mass of the mixture, and the amount of tailings added is 10.5~24%. Tailings slag needs to be used in combination with steel slag. It can be seen that the use of slag alone may require further treatment to increase compatibility with polymer materials, such as regulating morphology, modification treatment, etc. Summary of the invention

[0006] The purpose of the present invention is to provide a method and application of lithium slag morphology control. The method dissolves lithium slag by caustic soda solution and adjusts the morphology of lithium slag recrystallization by morphology control agent. The method can control the demand for lithium slag and improve the utilization rate of lithium slag. The method has strong practicality and good comprehensive benefits.

[0007] In order to achieve the above object, the present invention adopts the following technical solution: A method for regulating the morphology of lithium slag comprises the following steps: (1) Prepare a caustic soda solution of a certain concentration; (2) soaking the lithium slag in water, drying and crushing it to a certain particle size; (3) mixing the lithium slag crushed in step (2) with the caustic soda solution in step (1), and adding a morphology control agent thereto to obtain a mixture; (4) subjecting the mixture obtained in step (3) to a hydrothermal reaction, and after the reaction is completed, separating the solid and the liquid to obtain lithium slag with a long columnar morphology.

[0008] Furthermore, in step (1), the caustic alkali is one of sodium hydroxide and potassium hydroxide or a mixture of the two, and the alkali concentration is 2.5-4 mol / L.

[0009] Furthermore, the lithium slag in step (2) is a mixture of lithium extraction slag and tailings of spodumene, lepidolite, ferrolithium mica, and petalite.

[0010] Furthermore, the particle size of the lithium slag after crushing in step (2) is ≤74 μm.

[0011] Furthermore, in step (3), the mass volume ratio of lithium slag to caustic soda solution is 10g:100ml.

[0012] Furthermore, the morphology control agent added in step (3) is NaCl, NaNO 3 、Na 2 SO 4 , CaO, Ca(OH) 2 One of them.

[0013] Furthermore, the mass ratio of the morphology control agent added in step (3) to the lithium slag is 3-6:10.

[0014] Furthermore, the conditions of the hydrothermal reaction in step (4) are 200-240° C., 250-400 rpm, and 2-6 h.

[0015] Furthermore, the lithium slag with long columnar morphology obtained by the method described above has an aspect ratio of 2-20:1, preferably 20:1.

[0016] Furthermore, the application of the long columnar lithium slag in the preparation of PVC composite materials is to compound the long columnar lithium slag into PVC material to prepare a lithium slag / PVC composite material.

[0017] Compared with the prior art, the advantages of the present invention are: (1) The present invention regulates the morphology of lithium slag, which can broaden the applicable environment of lithium slag. It can not only effectively alleviate the pollution problem caused by large-scale storage of lithium slag, but also realize the resource utilization of lithium slag from lithium mica to obtain high-value-added lithium slag / PVC composite materials, providing more directions for the resource utilization of lithium slag from lithium mica.

[0018] (2) By regulating the morphology, lithium slag morphology that is more conducive to the modification of PVC materials can be screened out, which is conducive to the use of lithium slag as a filler alone and adding a higher proportion of lithium slag to PVC materials, further reducing the pollution caused by accumulation to the environment.

[0019] (3) The process is short and easy to realize industrial production. The main process of this method is to mix lithium slag with caustic soda and morphology control agent for hydrothermal reaction. The process is simple and has low requirements on process conditions, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 These are microscopic morphologies of the regulated lithium slag in the present invention; (a) regulated lithium slag 1; (b) regulated lithium slag 2; (c) regulated lithium slag 3; (d) regulated lithium slag 4. DETAILED DESCRIPTION

[0021] Application of long columnar lithium slag in the preparation of PVC composite materials: Long columnar lithium slag is compounded into PVC material to prepare lithium slag / PVC composite materials. Specifically, long columnar lithium slag, polyvinyl chloride, aluminate coupling agent, processing aid MC100, calcium zinc composite stabilizer, lubricant PE wax are mixed in a mass ratio of 10:50:0.11:1.4:1.2:2.1, extruded and granulated by a twin-screw extruder, and a composite material of lithium slag and PVC is prepared.

[0022] The method for preparing the long columnar lithium slag comprises the following steps: (1) Prepare a caustic soda solution of a certain concentration.

[0023] (2) Soak the untreated lithium slag in water, dry it and crush it to a certain particle size.

[0024] (3) The lithium slag crushed in step (2) is mixed with the caustic soda solution in step (1), and a morphology control agent is added thereto to obtain a mixture.

[0025] (4) subjecting the mixture obtained in step (3) to a hydrothermal reaction, and after the reaction is completed, separating the solid and the liquid to obtain lithium slag with a long columnar morphology.

[0026] Furthermore, in step (1), the caustic alkali is one of sodium hydroxide and potassium hydroxide or a mixture of the two, and the alkali concentration is 2.5-4 mol / L.

[0027] Furthermore, the lithium slag in step (2) is a mixture of lithium extraction slag from spodumene, lepidolite, ferrolithium mica or petalite and tailings.

[0028] Furthermore, the particle size of the lithium slag after crushing in step (2) is ≤74 μm.

[0029] Furthermore, in step (3), the mass volume ratio of lithium slag to caustic soda solution is 10g:100ml.

[0030] Furthermore, (3) the added morphology control agent is sodium salt (NaCl, NaNO 3 、Na 2 SO 4 ) or CaO, Ca(OH) 2 One of them.

[0031] Furthermore, the mass ratio of the morphology control agent added in step (3) to the lithium slag is 3-6:10.

[0032] Furthermore, the conditions of the hydrothermal reaction in step (4) are 200-240° C., 250-400 rpm, and 2-6 h.

[0033] The present invention is further described in detail below through specific implementation methods, but the present invention is not limited thereto. Various changes and substitutions made by those skilled in the art based on the present invention should all fall within the scope of the claims attached to the present invention as long as they do not depart from the spirit of the present invention.

[0034] Example 1 (1) Dissolve 10 g of sodium hydroxide in 100 ml of water to prepare a 2.5 mol / L sodium hydroxide solution.

[0035] (2) The lithium slag was soaked, dried and crushed, and 10 g of lithium slag crushed to a particle size of ≤74 μm and 3.55 g of morphology control agent (Na 2 SO 4 ) is added to the sodium hydroxide solution in (1), placed in a reactor, and the reaction conditions are set at 230°C, 300 rpm, and 5 h.

[0036] (3) After the reaction is completed, solid-liquid separation is performed, and the filter residue is stirred and washed twice with water at a ratio of 1g:10ml, and solid-liquid separation is performed again. After drying and grinding, the regulated lithium slag 1 is obtained. The morphology of the regulated lithium slag 1 is characterized by a long columnar shape with an aspect ratio of about 20:1.

[0037] (4) Take the regulated lithium slag 1, polyvinyl chloride, aluminate coupling agent, processing aid MC100, calcium zinc composite stabilizer, and lubricant PE wax in (3) at a mass ratio of 10:50:0.11:1.4:1.2:2.1. Add them into a high-speed mixer for premixing, and then extrude and granulate them through a twin-screw extruder to prepare a composite material of lithium slag and PVC.

[0038] Example 2 (1) Dissolve 15 mol / L of sodium hydroxide in 100 ml of water to prepare a 3.75 mol / L sodium hydroxide solution.

[0039] (2) The lithium slag was soaked, dried and crushed, and 10 g of lithium slag crushed to a particle size of ≤74 μm and 3.55 g of morphology control agent (Na 2 SO 4 ) is added to the sodium hydroxide solution in (1), placed in a reactor, and the reaction conditions are set at 230°C, 300 rpm, and 5 h.

[0040] (3) After the reaction is completed, solid-liquid separation is performed, and the filter residue is stirred and washed twice with water at a ratio of 1g:10ml, and solid-liquid separation is performed again. After drying and grinding, the regulated lithium slag 2 is obtained. The morphology of the regulated lithium slag 2 is characterized by a long columnar shape with an aspect ratio of about 10:1.

[0041] (4) Take the regulated lithium slag 2, polyvinyl chloride, aluminate coupling agent, processing aid MC100, calcium zinc composite stabilizer, and lubricant PE wax in (3) at a mass ratio of 10:50:0.11:1.4:1.2:2.1. Add them into a high-speed mixer for premixing, and then extrude and granulate them through a twin-screw extruder to prepare a composite material of lithium slag and PVC.

[0042] Example 3 (1) Dissolve 20 g of sodium hydroxide in 100 ml of water to prepare a 5 mol / L sodium hydroxide solution.

[0043] (2) The lithium slag was soaked, dried and crushed, and 10 g of lithium slag crushed to a particle size of ≤74 μm and 3.55 g of morphology control agent (Na 2 SO 4 ) is added to the sodium hydroxide solution in (1), placed in a reactor, and the reaction conditions are set at 230°C, 300 rpm, and 5 h.

[0044] (3) After the reaction is completed, solid-liquid separation is performed, and the filter residue is stirred and washed twice with water in a ratio of 1 g:10 ml, and solid-liquid separation is performed again. After drying and grinding, the regulated lithium slag 3 is obtained. The morphology of the regulated lithium slag 3 is characterized by a long columnar shape with an aspect ratio of about 10:3~4.

[0045] (4) Take the regulated lithium slag 3, polyvinyl chloride, aluminate coupling agent, processing aid MC100, calcium zinc composite stabilizer, and lubricant PE wax in (3) at a mass ratio of 10:50:0.11:1.4:1.2:2.1. Add them into a high-speed mixer for premixing, and then extrude and granulate them through a twin-screw extruder to prepare a composite material of lithium slag and PVC.

[0046] Comparative Example 1 (1) Dissolve 20 g of sodium hydroxide in 100 ml of water to prepare a 5 mol / L sodium hydroxide solution.

[0047] (2) The lithium slag is soaked in water, dried and crushed, 10 g of lithium slag crushed to a particle size of ≤74 μm and 5 g of a morphology control agent (CaO) are added to the sodium hydroxide solution in (1), and placed in a reactor. The reaction conditions are set to 230°C, 300 rpm, and 5 h.

[0048] (3) After the reaction is completed, solid-liquid separation is performed, and the filter residue is stirred and washed twice with water in a ratio of 1 g:10 ml, and solid-liquid separation is performed again. After drying and grinding, the regulated lithium slag 4 is obtained. The morphology of the regulated lithium slag 4 is octahedral, and the aspect ratio is about 1-1.5:1.

[0049] (4) Take the regulated lithium slag 4, polyvinyl chloride, aluminate coupling agent, processing aid MC100, calcium zinc composite stabilizer, and lubricant PE wax in (3) at a mass ratio of 10:50:0.11:1.4:1.2:2.1. Add them into a high-speed mixer for premixing, and then extrude and granulate them through a twin-screw extruder to prepare a composite material of lithium slag and PVC.

[0050] Comparative Example 2 Take polyvinyl chloride, processing aid MC100, calcium zinc composite stabilizer, and lubricant PE wax in a mass ratio of 50:1.4:1.2:2.1. Add them into a high-speed mixer for premixing, and then extrude and granulate them through a twin-screw extruder to prepare pure PVC material.

[0051] The mechanical properties of materials prepared by composite materials of lithium slag with different morphologies and PVC were tested.

[0052] According to the test results, when the morphology of the lithium slag is controlled to be long columnar and the aspect ratio is larger, the effect of improving the mechanical properties of the PVC composite material is more obvious. When the aspect ratio of the lithium slag gradually decreases, the reinforcement effect on the PVC composite material gradually weakens.

[0053] In order to make the above features and advantages of the present invention more clearly understood, the following embodiments are given for detailed description. The methods of the present invention are all conventional methods in the art unless otherwise specified.

Claims

1. A method for regulating the morphology of lithium slag, characterized in that: The following steps are involved: (1) Prepare a caustic soda solution of a certain concentration; (2) soaking the lithium slag in water, drying and crushing it to a certain particle size; (3) mixing the lithium slag crushed in step (2) with the caustic soda solution in step (1), and adding a morphology control agent thereto to obtain a mixture; (4) subjecting the mixture obtained in step (3) to a hydrothermal reaction, and after the reaction is completed, separating the solid and the liquid to obtain lithium slag with a long columnar morphology.

2. The method according to claim 1, characterized in that: In step (1), the caustic alkali is one of sodium hydroxide and potassium hydroxide or a mixture of the two, and the alkali concentration is 2.5-4 mol / L.

3. The method according to claim 1, characterized in that: The lithium slag in step (2) is a mixture of lithium extraction slag from spodumene, lepidolite, ferrolithium mica, and petalite, and tailings.

4. The method according to claim 1, characterized in that: The particle size of the lithium slag after crushing in step (2) is ≤74 μm.

5. The method according to claim 1, characterized in that: In step (3), the mass volume ratio of lithium slag to caustic soda solution is 10g:100ml.

6. The method according to claim 1, characterized in that: The morphology control agent added in step (3) is one of NaCl, NaNO3, Na2SO4, CaO, and Ca(OH)2.

7. The method according to claim 1, characterized in that: The mass ratio of the morphology control agent added in step (3) to the lithium slag is 3-6:

10.

8. The method according to claim 1, characterized in that: The conditions of the hydrothermal reaction in step (4) are 200-240° C., 250-400 rpm, and 2-6 h.

9. The lithium slag having a long columnar morphology obtained by the method according to claim 1 is characterized in that: The aspect ratio of the long columnar morphology of lithium slag is 2-20:

1.

10. The use of the long columnar lithium slag in the preparation of PVC composite materials according to claim 9, characterized in that: Lithium slag with long columnar morphology is compounded into PVC material to prepare lithium slag / PVC composite material.

Citation Information

Patent Citations

  • Permanent antistatic molding composition and preparation method thereof

    CN101987897A

  • High-strength weather-resistant composite material and preparation process thereof

    CN117384453A

  • Morphology regulating agent, preparation method and application thereof

    CN107640753A

  • Comprehensive utilization method for directly extracting lithium by silicate-based lithium-containing ore acid process

    CN110526250A

  • Preparation method of modified slag composite material

    CN115141440A